Double exposure time averaged in-line digital holography - Singh, Vijay Raj (2011)
Theory, analysis and applications of digital in-line holography are presented for metrological applications. Particularly time averaged in-line digital holography is explored for dynamic characterization of membranes and MEMS diaphragms. The analysis and capability of numerically reconstructed amplitude and phase information from time averaged holograms is presented. Reconstructed amplitude provides the vibration mode shapes by showing the time average fringes that are modulated by zero-order Bessel function, same as in conventional time-averaged holography. However the numerical phase information divided in two parts, the first part represents the surface roughness information of object and is a source of noise for single exposure, and the second part called the time average phase. By using a novel double exposure method, the reconstructed phase information from time averaged holograms can be used for mean static deformation as well for better visualization of time averaged fringes. In case of the vibrating objects with simultaneous mean static deformation, the phase information mixes together and used for precise analysis of vibration behaviors. The use of double exposure method also suppress the noise from the real image wave, caused by overlapping of zero-order term and twin image wave because of in-line geometry. The experimental results are presented for vibrations of aluminum membrane with 10mm in size, and also for a MEMS diaphragm with 6mm in size.